(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The modern world, and especially Ukraine, is faced with unprecedented challenges caused by a full-scale war. These circumstances have radically changed the conditions for the functioning of all sectors of the economy, including the activities of enterprises. In wartime, financial strategies that were effective in peacetime lose their relevance, requiring immediate adaptation and rethinking. The ability of enterprises to quickly respond to changing conditions, reorient their activities, and ensure financial sustainability becomes critically important for survival and further development. Purpose: to analyze the main challenges faced by Ukrainian enterprises in wartime, to identify key areas for adapting their financial strategies, and to develop recommendations for the formation of sustainable financial mechanisms to ensure effective functioning and recovery in the post-war period. Methods. In the process of preparing this article, a complex of general scientific methods of scientific knowledge was used, which allowed for a comprehensive analysis of the problem of adapting financial strategies of enterprises in wartime and post-war recovery. Among the general scientific methods used were: the method of systems analysis - to study financial strategies as a holistic system of elements interconnected with each other and the external environment, which made it possible to consider the impact of military actions on all components of the financial activities of enterprises; the method of logical generalization and abstraction - for the formation of theoretical propositions regarding the essence of financial strategies in crisis conditions and their adaptation, as well as for the derivation of general patterns and trends. Results. The study identified key aspects of adapting financial strategies of enterprises in the context of war and post-war recovery, confirming the need for a radical reorientation of financial management. Conclusions. Successful adaptation of financial strategies is critical for the survival and effective recovery of enterprises during and after war. The results obtained can serve as a basis for informed financial decisions and the formation of a sustainable foundation for the future development of Ukrainian businesses.